“Momma, Today We Were Indian Chiefs!” Pathways to Kan’nikonhrí:io† Through Indigenous Holistic Education - White, Louellyn (Frontiers in Education, 2022)
The compartmentalization of knowledge and of mind, body, and spirit to schooling is the antithesis of Indigenous epistemologies and the philosophical and relational aspects of assessment making. For Indigenous students, this contributes to the cultural mismatch between home and school. In the classroom there is continued focus on colonial methods of assessment and little emphasis on children’s natural processes of learning. Assessments highlight what students know, rather than how they know. Assessments impact student’s self-esteem, self-confidence, and influence their future prospects during their educational journey. Public education and its emphasis on grading and standardized tests as measures of learning, neglect to understand the unique and diverse ways of knowing that children come to their classrooms with. Kan’nikonhrí:io (Good Mind) means to move through life with respect, dignity, honor and responsibility and is necessary for becoming fully Kanien’kehá:ka or Onkwehón:we (Original People). Non-Indigenous educators and institutions serving non-Indigenous students can benefit from the inclusion of Indigenous perspectives and epistemologies through raising awareness of Indigenous peoples history and contemporary realities, while enhancing a better understanding of the increasing cultural and learning diversity of student bodies. When children can bring their whole selves to their learning experience, including their spirits, while connecting the larger community, they can feel motivated for self-discovery through their lifelong adventure in learning, and they can be uplifted as they grow to be whole human beings with Kan’nikonhrí:io (Good Minds) and kind hearts. In this article, I offer a reflection on Indigenous holistic education and advocate for Indigenous epistemologies in public education including assessment practices as a way to address the TRC Calls to Action. Adapted from the AFS model, I offer a modified example of Indigenous holistic education here.